The Political Economy of the Sustainable Development Goals (SDGs): Does Performance on the SDGs Affect Re-Election? - Christian Kroll; Vera Zipperer (Sustainability, 2020)
While the economic voting hypothesis is a well-researched approach to explain behavior at the ballot box, a broader perspective of economic, social and environmental issues regarding a government's chances to get re-elected is still missing in the literature. In this context, this paper makes use for the first time of the Agenda 2030 with its 17 Sustainable Development Goals (SDGs) as the comprehensive policy framework that all 193 UN member states have pledged to achieve. The objective of our study is therefore to examine the relationship between SDGs' progress and the likelihood of re-election. Our analysis of 124 countries regarding performance on the SDGs over time and voting behavior shows: the chance to get re-elected as a government significantly increases for progress made towards SDG 5 (Gender Equality). Notable differences are also found for high-income vs. low-income countries. The fact that governments are rewarded at the ballot box for successful action towards gender equality is encouraging, while the mechanisms behind other SDG areas deserve more research.
Keywords: 330; sustainable development goals; political economy; voting behavior; economic voting; re-election; gender equality; sustainability